Saturday

April 19, 2014

April 19, 2014

Posted by **Gilda** on Tuesday, October 4, 2011 at 5:48am.

Expand and Simplify 3(3x-y)^2

- Maths -
**Reiny**, Tuesday, October 4, 2011 at 8:17am3(3x-y)^2

= 3(3x-y)(3x-y)= 3(9x^2 - 3xy - 3xy + y^2)

= 27x^2 - 18xy + 3y^2

**Related Questions**

maths - Solve 5x + 3y = 4 3x + 4y = 9 Just a bit confused Please help

French - Is it more common to use the expression "poser des questions à qn" vs "...

PLEASE HELP! Maths - Qn: the equation of the tangent to the curve y=kx+(6/x) at ...

maths - given that x+1/x=3 (a) expand (x+1/x)^3 and use your expansion to show ...

Maths B - Hi, i was just wondering if you could help me with how to work out ...

Maths Important - How would you draw the graph of this x^2/16 + y^2 = 1 ( this ...

Biology - I am a bit confused about conjugation, transduction and transformation...

Maths - Expand ln(1+x) and ln(1-x) and hence deduce that ln((y+1)/(y-1))=[2/y]+[...

maths - expand 5(3w^2+4)

Maths - (x+5)(x-1) Expand the brackets